Peran Ibu dalam Menumbuhkan Ekoliterasi pada Anak Kelompok B TKIT Azkia Aceh Besar - Syahrina, Alfi; Faridy, Faizatul (UIR PRESS, 2024)
Growing awareness of loving the environment in early childhood is an investment for the future. When children are raised by taking care of the environment, the environment will take care of them in the future, and vice versa. The aim of this research is to analyze the role of mothers in fostering ecoliteracy in TKIT Azkia group B children. This research uses qualitative methodology. Data collection methods are interviews, observation and separate document analysis. The results of this research are that mothers provide examples and get children used to using enough water, turning off the water tap after use, cooking for children and providing tumblers for children to drink in, thus minimizing children's frequent snacks outside and the use of single-use plastic bottles.